Assessing the differences in the impact of corporate wellness programmes in Singapore between private and public organizations on job satisfaction, presenteeism and organizational citizenship behaviour. - Koh, Hui Min. (2008)
This research project focuses on three outcomes of Corporate Wellness Programmes (CWP), namely, Job Satisfaction, Organizational Citizenship Behaviour (OCB) and Presenteeism. A quantitative studywas conducted with a sample population of 13 organizations in Singapore. Results indicated that there is a difference in the increase in presenteeism brought about by CWP between the public and private sector. Positive relationships were observed between the three outcomes.